2013
DOI: 10.3399/bjgp13x665198
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim prescription and subsequent resistance in childhood urinary infection: multilevel modelling analysis

Abstract: BackgroundAntibiotic resistance is a growing concern and antibiotic usage the main contributing factor, but there are few studies examining antibiotic use and resistance in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…5 Consistent with our previous review, we found some evidence from Duffy and colleagues of decreasing resistance for increasing time from antibiotic prescribing. 24 Policy, clinical, and research implications Our findings detail global high level resistance to some of the most commonly prescribed antibiotics for children primary care, which could result in several drugs becoming ineffective first line treatments in many countries. The Infectious Diseases Society of America (IDSA) in collaboration with the European Society for Microbiology and Infectious Diseases (ESCMID) 95 recommend that an antibiotic should be selected for first line empirical treatment of urinary tract infection only if the local prevalence of resistance is less than 20%.…”
Section: Association Between Previous Antibiotic Exposure and Bacterimentioning
confidence: 90%
See 2 more Smart Citations
“…5 Consistent with our previous review, we found some evidence from Duffy and colleagues of decreasing resistance for increasing time from antibiotic prescribing. 24 Policy, clinical, and research implications Our findings detail global high level resistance to some of the most commonly prescribed antibiotics for children primary care, which could result in several drugs becoming ineffective first line treatments in many countries. The Infectious Diseases Society of America (IDSA) in collaboration with the European Society for Microbiology and Infectious Diseases (ESCMID) 95 recommend that an antibiotic should be selected for first line empirical treatment of urinary tract infection only if the local prevalence of resistance is less than 20%.…”
Section: Association Between Previous Antibiotic Exposure and Bacterimentioning
confidence: 90%
“…As data reported in the UK study were analysed with a two level model of samples nested within patients, we reported it separately in our meta-analysis. 24 All studies were observational; 25 were retrospective, six prospective, and two case-control. Thirty reported information on prevalence of resistance in E coli urinary tract infection isolates, with the three remaining reporting the association between previous antibiotic exposure and E coli resistance only.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step up Duffy et al 4 who, in this month's BJGP, have published an article showing that bacterial resistance to trimethoprim in children's UTI is:…”
mentioning
confidence: 99%
“…3 Yet curiously, antibiotic-induced resistance attenuates over time. 4 For the first few months after taking an antibiotic, urine infections are five times more likely to be antibiotic resistant. Within 6 months of taking an antibiotic, the rate of resistance reverts to pre-treatment levels.…”
mentioning
confidence: 99%